ON THE STRUCTURE OF PULSAR AXISYMMETRIC FORCE-FREE MAGNETOSPHERE BEYOND THE LIGHT CYLINDER - Petrova, S. A. (Видавничий дім «Академперіодика», 2013)
An exact multipolar solution of the pulsar equation is found,which corresponds to the field of a monopole shifted along themagnetic axis. Based on this solution, the split-offset monopolemodel is developed, which, as compared to the classicalsplit monopole model, better represents the force-free structureof the pulsar dipolar magnetosphere beyond the light cylinder.In particular, it allows to include the outer gap into theglobal magnetospheric structure. On the analogy of this model,a new scheme of the pulsar force-free magnetosphere is suggested,which for the first time self-consistently incorporatesthe polar, outer and slot gaps. The gaps are believed to playan important role in the pulsar current circuit closure. Theimplications of our results for different fields of pulsar researchare outlined.